Advances in the study of the correlation between insulin resistance and infertility - Lei, Ruobing; Chen, Shuyi; Li, Weihong (Frontiers in Endocrinology, 2024)
is not only involved in the development of various metabolic diseases, but also affects female reproductive function, and to some extent is closely related to female infertility. IR may increase the risk of female infertility by activating oxidative stress, interfering with energy metabolism, affecting oocyte development, embryo quality and endometrial tolerance, affecting hormone secretion and embryo implantation, as well as affecting assisted conception outcomes in infertile populations and reducing the success rate of assisted reproductive technology treatment in infertile populations.In addition, IR is closely associated with spontaneous abortion, gestational diabetes and other adverse pregnancies, and if not corrected in time, may increase the risk of obesity and metabolic diseases in the offspring in the long term. This article provides a review of the relationship between IR and infertility to provide new ideas for the treatment of infertility. 【Keywords】Insulin resistance1, infertility2, assisted reproductive technology3, adverse pregnancy outcomes4, offspring health5 Metabolic Syndrome (MetS) is a group of pathological syndromes characterized by insulin resistance, abdominal obesity, hypertension and hyperlipidemia, and this